2012
DOI: 10.1038/ngeo1622
|View full text |Cite
|
Sign up to set email alerts
|

A Laurentide outburst flooding event during the last interglacial period

Abstract: (Fig. 1). The red layer is ∼10 cm thick at Site U1305 and ∼20 cm thick at U1302 (Figs 2-4). The base of the layer is very sharp at both sites, suggesting rapid onset of deposition with little bioturbation. At Site U1305, the top of the layer is well defined, whereas at Site U1302 the top of the layer is more diffuse with a distinct tail, probably the result of mixing by bioturbation. The bright red colour of the layer is distinctive and marked by anomalously high values of a * (red-green colour parameter) at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 31 publications
3
44
0
Order By: Relevance
“…Indeed, the smaller size of the LIS is consistent with changes in large-scale atmospheric circulation that facilitated the development of a larger Eurasian Ice Sheet during MIS 6 (Colleoni et al, 2016). Little is known about the deglaciation of the LIS at the end of MIS 6, but a major glacial lake outburst flood has been reported from a proximal marine core in the Labrador Sea around 124 ka (Nicholl et al, 2012), which may be analogous to the widely reported drainage of glacial Lake Agassiz during the final deglaciation of the LIS around 8.2 ka (e.g. Barber et al, 1999).…”
Section: Inception and Build-up To Its Last Glacial Maximummentioning
confidence: 73%
“…Indeed, the smaller size of the LIS is consistent with changes in large-scale atmospheric circulation that facilitated the development of a larger Eurasian Ice Sheet during MIS 6 (Colleoni et al, 2016). Little is known about the deglaciation of the LIS at the end of MIS 6, but a major glacial lake outburst flood has been reported from a proximal marine core in the Labrador Sea around 124 ka (Nicholl et al, 2012), which may be analogous to the widely reported drainage of glacial Lake Agassiz during the final deglaciation of the LIS around 8.2 ka (e.g. Barber et al, 1999).…”
Section: Inception and Build-up To Its Last Glacial Maximummentioning
confidence: 73%
“…Hysteresis ratios: M r /M s and H cr /H c where M r is saturation remanence, M s is saturation magnetization, H cr is coercivity of remanence, and H c is coercive force, can be used to delineate single domain (SD), pseudo- single domain (PSD) and multidomain (MD) magnetite and to assign "mean" magnetite grain sizes through empirical and theoretical calibrations of the so-called Day plot (Day et al, 1977;Carter-Stiglitz et al, 2001;Dunlop, 2002;Dunlop and CarterStiglitz, 2006). Magnetic hysteresis properties were also analyzed through First-Order Reversal Curves (FORCs) that provide enhanced mineral and domain state discrimination (Pike et al, 1999;Roberts et al, 2000;Muxworthy and Roberts, 2007). FORCs are carried out by progressively saturating a small (few hundred mg) sample in a field (H sat ), decreasing the field to a value H a , reversing the field and sweeping it back to H sat in a series of regular field steps (H b ).…”
Section: Rock Magnetismmentioning
confidence: 99%
“…2). The last and most prominent of the NADW anomalies during the early LIG (at ~124 ka) was also associated with an outburst flood analogous to the one believed to have triggered the 8.2 ka event, when large amounts of freshwater entered the North Atlantic through the Labrador Sea (Nicholl et al 2012;Galaasen et al 2014). Taken together, this highlights buoyancy gain from a generally warm Galaasen et al (2014).…”
Section: Nadw Variability During the Ligmentioning
confidence: 99%